150th anniversary of clinical description of multiple sclerosis: Leopold Ordenstein's legacy. (29th May 2018) - Lehmann, Helmar C.; Compston, Alastair; Hartung, Hans-Peter
Abstract : The clinical features of multiple sclerosis were first defined in detail and with pathologic confirmation in a medical thesis published at the Salpêtrière, Paris, in 1868. The author, Leopold Ordenstein (1835–1902), a German physician, analyzed cases collected by his mentor, Jean-Martin Charcot (1825–1893). The 2 clinician-scientists described the characteristic symptoms, predisposing age, and pathologic features of the disease, and emphasized the clear delineation from other chronic progressive disorders, especially paralysis agitans. The latter was referred to as Parkinson disease by William Sanders in 1865 and adopted by Désiré-Magloire Bourneville on behalf of Charcot in 1875. This essay commemorates the 150th anniversary of the publication of the pioneering work of Leopold Ordenstein and Jean-Martin Charcot.